Reflexivity through practice-informed student journals: how "sustainable wellbeing" relates to teleoaffectivities. Issue 1 (9th December 2022) - Sahakian, Marlyne; Stroude, Aurianne; Godin, Laurence; Courtin, Irène; Fahy, Frances; Fuchs, Doris; Langlois, Justine
Abstract: The COVID-19 pandemic that first swept across the world in 2020 led to disruptions in habits and routines—central themes in social practice approaches to consumption. Teaching was also disrupted: the move to online classes forced the development of new modalities of teaching and learning. As a result, a group of social science instructors in a "sustainable consumption" network came together to engage students in a reflexivity exercise through weekly journal entries at four universities located in Switzerland, Germany, and Ireland. The students were invited to document how their everyday practices were changing, and how these reported changes related to "sustainable wellbeing." Further, they were encouraged to reflect on how notions of the collective were reimagined in light of the uncertain sanitary situation. Our analyses show how individual wellbeing is tied to time and social interactions, which are both structured by spatial arrangements. We also discuss how students situate changes in relation to broader, societal trends, hinting at how "sustainable wellbeing" contrasts with other teleoaffective formations such as economic health. We conclude with a discussion around the implications of the journaling method in relation to other participatory processes toward the normative aim of a good life for all.